Tourism Village Concept Assistance and Mentoring in Karawang - Sumarni, Neni; Arisandi, Vidya; Fajrin, Yeni (Jurnal Pengabdian Masyarakat, 2025)
Purpose: The goal of this community service is to develop a tourist village in Karawang. Karawang, with its significant tourism potential, does not yet have a tourist village officially recognized by the local government through a Regent's Decree on Tourist Villages. Method: In this community service, the community service team provides assistance to villages with tourism potential that meet the criteria. The methods used include outreach, training, and mentoring to develop them into tourist villages. Practical Applications: This process is carried out with the involvement of Pokdarwis and tourism managers as well as the tourism office. Conclusion: The results of the community service stated that eight villages in Karawang were declared as tourist villages, each with its own criteria and unique tourism characteristics.